Rainfall-induced unstable slope monitoring and early warning through tilt sensors - Sheikh, Md Rasel; Nakata, Yukio; Shitano, Munehiko; Kaneko, Masahiro (Soils and Foundations, 2021)
•A rainfall-induced slope instability monitoring and early warning system is proposed.•Tilt sensors are utilized as slope deformation monitoring devices.•An advanced time prediction model, based on real-time monitoring data, is established. Real-time unstable slope monitoring is essential for recognition of landslide occurrence, as well as for early warning to reduce landslide-induced damages. This study investigated an unstable slope monitoring system that consists of tilt sensors aiming to establish an advanced time prediction model (TPM) for landslide early warning. The monitoring process utilized additional support devices (e.g. pipe strain gauges, water level gauges and a rain gauge) installed on a natural cut slope site. The tilt sensors could detect movements (in tilt angle) within the slope generated by heavy rains. Analysis of the recorded data revealed that the rate of movement, or tilt, was influenced by groundwater table fluctuations and antecedent rainfalls. A relationship between the tilt rate and the horizontal displacement calculated from pipe strain value has been established. Subsequently, a new classification of slope movement was proposed according to the tilt rates obtained from the deformation process of the slope. Considering the movement characteristics, two warning levels were identified such as warning and evacuation. Further, an advanced TPM was proposed in relation to realtime slope surface tilt rates. The TPM could provide efficient results at the continuous acceleration phase of the landslide occurrence. Therefore, we suggest this technique can be applied for monitoring and early warning of rainfall-induced shallow landslides.